Aerobic and anaerobic mineralization of Salvinia molesta and Myriophyllum aquaticum leachates from a tropical reservoir (Brazil) - Silva,Renato Henriques da (2011)
AIM: This study aimed at describing and discussing the leachates mineralization (aerobic and anaerobic) of two species of aquatic macrophytes (Salvinia molesta and Myriophyllum aquaticum) from a tropical reservoir (22° 00' S and 47° 54' W); METHODS: The incubations were prepared with plant leachates and reservoir water sample and were maintained during 45 days in the dark (at 20 °C). The organic carbon and the oxygen consumption kinetics were evaluated; RESULTS: Irrespective of to the experimental condition, the leachates were mainly utilized for catabolic processes (i.e., respiration), mineralization was slightly faster in an aerobic environment (1.22 fold) and in this condition, the yield of refractory products was smaller (2.3%); the O/C stoichiometric ratios values (oxygen consumed per atom of carbon) from mineralization of the 2 types of leachates were similar (ca. 1.12); CONCLUSIONS: According to these results we conclude that the leachate from selected macrophytes is rapidly decomposed and subsidize primariy the microbial catabolism (aerobic or anaerobic); in addition, we propose that S. molesta contributes more to the input of dissolved organic matter within the reservoir.